More Missing Women, Fewer Dying Girls: The Impact of Sex-Selective Abortion on Sex at Birth and Relative Female Mortality in Taiwan. Issue 4 (1st August 2014) - Lin, Ming-Jen; Liu, Jin-Tan; Qian, Nancy
Abstract: This study finds that the introduction of sex-selective abortion in Taiwan due to the legalization of abortion when prenatal sex-detection technology was already available increased the fraction of males born at higher parities and changed the composition of mothers choosing to give birth. Controlling for compositional changes, we find that access to sex-selective abortion reduced relative neonatal female mortality rates for higher-parity births.